Cushing’s Syndrome: A Historic Review of the Treatment Strategies and Corresponding Outcomes in a Single Tertiary Center over the Past Half-Century - Nankova, Anelia; Yaneva, Maria; Elenkova, Atanaska; Tcharaktchiev, Dimitar; Marinov, Marin; Hadzhiyanev, Asen; Sechanov, Tanyo; Gantchev, Georgi; Todorov, Georgi; Kirilov, Georgi; Kalinov, Krasimir; Andreeva, Maria; Zacharieva, Sabina (Hormone and Metabolic Research, 2018)
Cushing’s syndrome (CS) is associated with serious comorbidities and an increased mortality rate that could be reduced only if strict biochemical control is achieved. The aim of this study was to show the 50-year experience of a single tertiary center in the management of CS patients – the different treatment modalities used over the years and the corresponding outcomes. It was a retrospective study of a large cohort of patients from the Bulgarian CS database: 613 patients (374 with ACTH-dependent and 239 with ACTH-independent CS). Pituitary surgery was applied to 242 patients with Cushing’s disease (CD) with initial remission rate of 74% of which 10% relapsed. Approximately 36% manifested with active disease during the long-term follow-up (26% with persistent disease, 10% relapses) most of which were subjected to a secondary treatment (13.6% to pituitary resurgery, 14% to pituitary radiotherapy, and 5.4% to bilateral adrenalectomy). A total of 294 CD patients received medical therapy with overall remission rates for the most commonly used drugs: dopamine agonists 20%, pasireotide 30%, and ketoconazole 63%. Significant improvement of results was achieved by combining drugs with different mechanisms of action. Regardless of the progress in the neurosurgery and radiotherapy techniques and new drugs discovery, the management of patients with CS remains a real challenge for physicians. Not only patients with adrenal carcinoma but also significant percentage of subjects with persistent and recurrent Cushing’s disease often require a polymodal approach and the efforts of a multidisciplinary highly qualified, experienced, and motivated team in order to achieve a long-term remission.
Keywords: Cushing’s disease; pituitary surgery; adrenalectomy; adrenal carcinoma